2017
DOI: 10.1016/j.str.2016.11.022
|View full text |Cite
|
Sign up to set email alerts
|

ATP-Induced Structural Remodeling in the Antiactivator FleN Enables Formation of the Functional Dimeric Form

Abstract: FleN, a P loop ATPase is vital for maintaining a monotrichous phenotype in Pseudomonas aeruginosa. FleN exhibits antagonistic activity against FleQ, the master transcriptional regulator of flagellar genes. Crystal structures of FleN in the apo form (1.66 Å) and in complex with β,γ-imidoadenosine 5'-triphosphate (1.55 Å) reveal that it undergoes drastic conformational changes on ATP binding to attain a structure capable of dimerization. Mutations of the residues that stabilize the binding of ATP were defective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…As FleN is a known inhibitor of the ATPase activity of FleQ ( 19 ), we further examined the ability of FleN to inhibit the ATPase activity of different domain constructs of FleQ. FleN reduces the ATPase activity of FleQ FL , FleQ AAA+ , and FleQ RECAAA+ by 80%, and the residual activity is similar to the ATPase activity of FleN ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As FleN is a known inhibitor of the ATPase activity of FleQ ( 19 ), we further examined the ability of FleN to inhibit the ATPase activity of different domain constructs of FleQ. FleN reduces the ATPase activity of FleQ FL , FleQ AAA+ , and FleQ RECAAA+ by 80%, and the residual activity is similar to the ATPase activity of FleN ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that ATP-mediated dimerization in FleN is essential for its antagonist effect over FleQ. It exerts this effect without affecting the DNA binding ability of FleQ ( 18 , 19 ). However, the lack of structural data on the protein-protein complex impedes a detailed understanding of the mechanism of transcription inhibition by antiactivators of σ 54 regulators in general and by FleN in particular.…”
Section: Introductionmentioning
confidence: 99%
“…FlhG is homologous to the MinD/ParA-type ATPases and shares significant structural and functional similarity (8,10); indeed, in C. jejuni FlhG plays the role of MinD in determining the site of cell division (11). Like MinD (12,13), FlhG forms ATPdependent homodimers that interact with the inner membrane through a C-terminal amphipathic helix or a membranetargeting sequence (MTS) (8,10). FlhG acts in concert with the signal recognition particle-GTPase FlhF and stimulates the GTPase activity of FlhF (14)(15)(16).…”
mentioning
confidence: 99%
“…Studies of P. aeruginosa FleN, an ortholog of FlhG, have established that FleN inhibits FleQ (the FlrA ortholog) by direct interaction (32)(33)(34). For Shewanella spp., a similar mechanism for the antagonistic effect of FlhG against FlrA was proposed recently (35).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, we found that the multiflagellum phenotype resulting from the deletion of flhG or flhFG is due to enhanced activity of FlrA. The association of FlhG with FlrA was initially established with the P. aeruginosa FlhG ortholog, FleN; FlhG and FleN share 35% sequence identity and are highly similar in structure (32)(33)(34). FleN exerts an containing 20 mM imidazole, the His-tagged FlhF variants were eluted in elution buffer containing 100 mM imidazole.…”
Section: Discussionmentioning
confidence: 99%